2009
DOI: 10.1063/1.3274811
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sorbed hydrogen on low-temperature radial thermal expansion of single-walled carbon nanotube bundles

Abstract: The effect of a normal H 2 impurity upon the radial thermal expansion α r of SWNT bundles has been investigated in the interval T = 2.2-27 K using the dilatometric method. It is found that H 2 saturation of SWNT bundles causes a shift of the temperature interval of the negative thermal expansion towards lower (as compared to pure CNTs) temperatures and a sharp increase in the magnitude of α r in the whole range of temperatures investigated. The low temperature desorption of H 2 from a powder consisting of bund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…However, our comparative experiments on saturating o-SWNT and c-SWNT bundles with H 2 [4] showed that the c-SWNTs absorbed more hydrogen than the oxidated ones. This was attributed to surface defects (mainly vacancies in the carbon structure) present in the CNTs of the starting powder before the oxidative treatment.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, our comparative experiments on saturating o-SWNT and c-SWNT bundles with H 2 [4] showed that the c-SWNTs absorbed more hydrogen than the oxidated ones. This was attributed to surface defects (mainly vacancies in the carbon structure) present in the CNTs of the starting powder before the oxidative treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, high concentrations of the sorbed gas were also observed in the H 2 -c-SWNT system [4] but the spatial distribution of the H 2 molecules in the SWNT bundles was evidently different. The H 2 molecules occupied the grooves at the bundle surface, the rest of the bundle surface and the interstitial channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impurity molecules dampen the low frequency transverse vibrations of the CNT walls and thus suppress the negative contribution to the thermal expansion. It was found [2][3][4] that the temperature dependences α r (T) taken on CNT bundles saturated with gas impurities had peaks which were attributed to a spatial redistribution of the impurity molecules in the grooves and on the surface of CNT bundles.It is known that the 4 He impurity has quite a significant effect on the thermal and structural properties of carbon nanomaterials, including fullerite C 60 [6].In this study we investigated the radial thermal expansion of bundles of single-walled carbon nanotubes with closed ends (c-SWNTs) saturated with 4He using the dilatometric method. The temperature interval was 2.1-9.5 K.…”
mentioning
confidence: 99%
“…Previously [1][2][3][4] we used the dilatometric method to investigate the low temperature radial thermal expansion of carbon nanotube (CNT) bundles and the effect of atomic (Xe) and molecular (H 2 , N 2 ) impurities on it. A number of effects have been detected, which are induced, on the one hand, by low frequency vibrations of individual CNTs and, on the other hand, by the collective behavior of the tubes forming a bundle.…”
Section: Introductionmentioning
confidence: 99%